Patterns of maternal control and their relations to the academic achievement of primary school children in San Jacinto, Masbate - Felipe, Flora V. 1941- (s.n.], 1969)
The aim of the study is to contribute information which will be useful in understanding Filipino children, at the same time filling in part the needs for local research on child-rearing practices. The study is designed to investigate the associational relationship of maternal control to academic achievement of primary school children.